Perceived value of internship experience: a try before you leap. Issue 4 (27th March 2018) - Bhattacharya, Sonali; Neelam, Netra
Abstract : Purpose: The purpose of this paper is to examine how internship value is manifested in the context of a business school. The authors have examined the internship experience in terms of experiential learning and employability. Specifically, the authors investigate the factors that determine internship at four phases: design, conduct, evaluation and feedback. Design/methodology/approach: The authors have applied a mixed method approach. In all, 110 students of a busines school were first surveyed on their expectation, motivation and level of preparation through a self-administered questionnaire before internship. Based on the survey result, eight of these students were interviewed in details about internship expectations from industry, the selection process for internship, communications or exchanges between intern and companies prior to internship and perceived industry expectation from interns. At the next phase, authors used a qualitative research approach by conducting semi-structured, in-depth interviews with 14 interns and their mentors after internship period. They were interviewed on design, conduct, evaluation and feedback process of the internship. Interviews tried capture what kind of leader-member exchange led to satisfactory internship experience and outcome from view of both inter and mentor. Findings: The authors find that at various stages of internship program quality of mentor – intern exchanges (as defined by leadership exchange theory), and task characteristics as indicated by autonomy, task variety, task significance and performance feedback determine intern's performance. An intern's performance is antecedent to an intern's and a mentor's satisfaction and overall internship value. The authors also found that intrinsic capability of intern such as critical thinking ability and learning orientation result in enhanced value of internship experience. The proposed models, postulate that at designing stage, lower the level of communication from employers, higher the feeling of ambiguity and lower the perceived internship value in terms of experiential learning and perceived employability. Feeling of ambiguity is moderated by existence of prior work experience of interns. At conduction stage, mentor-intern exchange is directly related to flexibility in structure of the program and inversely related to dependency on peer learning. Mentor-intern exchange also related to mentor and intern's learning value. However, the learning value is moderated by learning orientation of the intern. Originality/value: The authors have tried the summer internship experience from the perspective of interns and mentors. This is the uniqueness of the research.